Resource Allocation Algorithm for the Downlink of Multi-User OFDM System with Optimized Fairness - Limei Tang; Haiyan Cao; Jun Li; Shiyi Xie (Dianxin kexue)
A resource allocation algorithm for the downlink of multi-user OFDM system with optimized fairness was studied. Firstly, assign the subcarriers to users with the constraint on proportional fairness and the water-filling algorithm was used in this process for the power allocation of each subcarrier. Then update the bits and power for each subcarrier of all the users using greedy power allocation to achieve higher data rates and power efficiency. Simulation results show that the proposed algorithm improves the capacity of the system while ensuring the performance of fairness better compared with the algorithm in[10]. To[12], the fairness is considerable improved with a little loss of capacity.